Hadith #2124 - Sunan Abi Dawud - Abdah bin Sulaiman al-Klabi عبدة بن سليمان الكلابي أبو محمد الكوفي; Ayoub al-Sakhtiyani أيوب السختياني; ibn Abbas; Ikrama عكرمة; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
When a man who has a wife married a virgin he should stay with her seven nights ; if he marries to a woman who has been previously married he should stay with her three nights. (The narrator said:) If I say that he (Anas) narrated this tradition from the Prophet (ﷺ) I shall be true. But he said: The Sunnah is so-and-so.
Grade: Sahih

Hadith #2154 - Sunan Abi Dawud - Abu 'Alqama أبو علقمة; Abu Sa'id al-Khudri; Qatada قتادة; Sa'id bin Abi Sa'id; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Ubaidullah bin 'Umar al-Qawariri عبيد الله بن عمر القواريري; Yazid bin Zari' يزيد بن زريع (Sunan Abi Dawud)
The aforesaid tradition has also been transmitted by Abu Hurairah through a different chain of narrators. This version adds “The fornication of ear is hearing.”
Grade: Sahih

Hadith #2167 - Sunan Abi Dawud - Abdul Hameed bin 'Abdur Rahman عبد الحميد بن عبد الرحمن بن زيد; al-Hakam bin 'Utayba الحكم بن عتيبة; ibn Abbas; Maqsim bin Bajra مقسم بن بجرة; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sa'id bin Abi Sa'id; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
Maimunah daughter of Al Harith said “When the Apostle of Allaah(ﷺ) intended to associate and lie with any of his wives who was menstruating, he ordered her to wrap up the lower garment(loin-cloth) and then he had association with her.
Grade: Sahih

Hadith #2259 - Sunan Abi Dawud - Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Sa'id bin Abi Sa'id; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The words narrated by Malik alone are: “and he attributed the child to the woman.” Yunus narrated from Al Zuhri on the authority of Sahl bin Sa’d in the tradition regarding li’an(invoking curses). He disowned her conception hence her child was attributed to her.
Grade: Sahih

Hadith #2262 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Amr bin al-Harith bin Ya'qub عمرو بن الحارث; Sa'id bin Abi Sa'id; Yazid bin 'Abdullah bin Usama B. al-Haad يزيد بن عبد الله بن أسامة بن الهاد (Sunan Abi Dawud)
A bedouin came to the Prophet (ﷺ), and said: My wife has given birth to a black son, and I disown him. He then narrated the rest of the tradition to the same effect.
Grade: Sahih

Hadith #2307 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; Amr bin al-'Aas; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Rja'a bin Hywh رجاء بن حيوة; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
I can invoke the curse of Allah on anyone who wishes: The smaller surat an-Nisa (i.e. Surat at-Talaq) was revealed after the verse regarding the waiting period of four months and ten days had been revealed.
Grade: Sahih

Hadith #2317 - Sunan Abi Dawud - Azrh bin 'Abdur Rahman عزرة بن عبد الرحمن بن زرارة الخزاعي; Muhammad bin Abi 'Adi محمد بن أبي عدي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة; Sa'id bin Abi Sa'id; Sa'id bin Jubayr سعيد بن جبير الأسدي (Sunan Abi Dawud)
Ibn ‘Abbas said “The verse concerning the payment of ransom stands valid for pregnant and sucking woman.”
Grade: Sahih

Hadith #2344 - Sunan Abi Dawud - Abu Hurairah; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) invited me to a meal shortly before dawn in Ramadan saying: Come to the blessed morning meal.
Grade: Sahih

Hadith #2361 - Sunan Abi Dawud - Abu Hurairah; Kaysan Abu Sa'id al-Muqbari كيسان أبو سعيد المقبري المدني; Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: Do not observe perpetual fasting. If any of you wants to observe perpetual fast, he should observe it until the dawn. They (the people) asked: You observe perpetual fast ? He replied: My position is not like that of yours. There is One Who gives me to eat, and there is One who gives me to drink.
Grade: Sahih

Hadith #2446 - Sunan Abi Dawud - Muhammad bin al-Minhal al-Darir محمد بن المنهال الضرير; Qatada قتادة; Sa'id bin Abi Sa'id; Yazid bin Zari' يزيد بن زريع (Sunan Abi Dawud)
I came to Ibn ‘Abbas who was leaning against his sheet of cloth in the Sacred Mosque (al-Masjid al-Haram). I asked him about fasting on the day of ‘Ashurah. He said: When you sight the moon of al-Muharram, count (the days). When the 9th of Muharram comes, fast from the morning. I said: Would Muhammad (ﷺ) observe this fast ? He replied: Thus Muhammad (ﷺ) used to fast.
Grade: Sahih

Hadith #2581 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Prophet (ﷺ) said: There must be no shouting or leading another horse at one’s side. Yahya added in his tradition: When racing for a wager.
Grade: Sahih

Hadith #2597 - Sunan Abi Dawud - Abu Hurairah; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Sa'id bin Abi Sa'id; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
Al-Muhallab ibn AbuSufrah said: A man who heard the Prophet (ﷺ) say: If the enemy attacks you at night, let your war cry be Ha-Mim. They will not be helped.
Grade: Sahih

Hadith #2618 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; al-Hasan al-Basri الحسن البصري; Ayash bin al-Walid al-Rqam عياش بن الوليد الرقام; Qatada قتادة; Sa'id bin Abi Sa'id; Samra bin Jundub (Sunan Abi Dawud)
Anas said “the Prophet(ﷺ) sent Busaisah as a spy to see what the caravan of Abu Sufyan was doing.”
Grade: Sahih

Hadith #2678 - Sunan Abi Dawud - Abu Hurairah; al-Laith bin Sa'd الليث بن سعد; Isa bin Hammad bin Muslim, Zaghba عيسى بن حماد بن مسلم أبو موسى زغبة; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) sent Abdullah ibn Ghalib al-Laythi along with a detachment and I was also with them. He ordered them to attach Banu al-Mulawwih from all sides at al-Kadid. So we went out and when we reached al-Kadid we met al-Harith ibn al-Barsa al-Laythi, and seized him. He said: I came with the intention of embracing Islam, and I came out to go to the Messenger of Allah (ﷺ). We said: If you are a Muslim, there is no harm if we keep you in chains for a day and night; and if you
Grade: Da'if

Hadith #2694 - Sunan Abi Dawud - Abu Talha Ansari; Anas ibn Malik; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة; Ruh bin 'Ubada bin al-'Ala' روح بن عبادة بن العلاء; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) then said: Return to them (Hawazin) their women and their sons. If any of you withholds anything from this booty, we have six camels for him from the first booty which Allah gives us. The Prophet (ﷺ) then approached a camel, and taking a hair from its hump said: O people, I get nothing of this booty, not even this (meanwhile raising his two fingers) but the fifth, and the fifth is returned to you, so hand over threads and needles. A man got up with a ball of hair i
Grade: Hasan

Hadith #2830 - Sunan Abi Dawud - Abu Hurairah; Ahmed bin 'Ubda bin Musa أحمد بن عبدة بن موسى; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Sa'id bin Abi Sa'id; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
A man called the Messenger of Allah (ﷺ): We used to sacrifice Atirah in pre-Islamic days during Rajab; so what do you command us? He said: Sacrifice for the sake of Allah in any month whatever; obey Allah, Most High, and feed(the people). He said: We used to sacrifice a Fara’ in pre-Islamic days, so what do you command us? He said: On every pasturing animal there is a Fara’ which is fed by your cattle till it becomes strong and capable of carrying load. The narrator Nasr said (in his versi
Grade: Sahih

Hadith #2831 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
Prophet (ﷺ) sa saying: There is no fara’ and ‘atirah.
Grade: Sahih

Hadith #2837 - Sunan Abi Dawud - al-Hasan al-Basri الحسن البصري; Muhammad bin Abi 'Adi محمد بن أبي عدي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة; Sa'id bin Abi Sa'id; Samra bin Jundub (Sunan Abi Dawud)
The Prophet (ﷺ) said: A boy is in pledge for his Aqiqah. Sacrifice is made for him on the seventh day, his head is shaved and is smeared with blood. When Qatadah was asked about smearing with blood, how that should be done, he said: When you cut the head (i.e. throat) of the animal (meant for Aqiqah), you may take a few hair of it, place them on its veins, and then place them in the middle of the head of the infant, so that the blood flows on the hair (of the infant) like a threat. Then its he
Grade: Sahih

Hadith #2926 - Sunan Abi Dawud - Ahmed bin Salah al-Masri أحمد بن صالح المصري; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Sa'id bin Abi Sa'id; Sufyan bin 'Uyaynah سفيان بن عيينة; Umar ibn al-Khattab (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) established an alliance (of brotherhood) between the Emigrants and the Helpers in our house. He was asked: Did not the Messenger of Allah (ﷺ) say: There is no alliance in Islam ? He replied: The Messenger of Allah (ﷺ) established an alliance between the Emigrants and the Helpers in our house. This he said twice or thrice.
Grade: Sahih

Hadith #3002 - Sunan Abi Dawud - Abu Hurairah; al-Laith bin Sa'd الليث بن سعد; Kaysan Abu Sa'id al-Muqbari كيسان أبو سعيد المقبري المدني; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: If you gain a victory over the men of Jews, kill them. So Muhayyisah jumped over Shubaybah, a man of the Jewish merchants. He had close relations with them. He then killed him. At that time Huwayyisah (brother of Muhayyisah) had not embraced Islam. He was older than Muhayyisah. When he killed him, Huwayyisah beat him and said: O enemy of Allah, I swear by Allah, you have a good deal of fat in your belly from his property.
Grade: Da'if

Hadith #3076 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; al-Hasan al-Basri الحسن البصري; Muhammad bin Bashr bin al-Farafsa محمد بن بشر بن الفرافصة العبدي; Qatada قتادة; Sa'id bin Abi Sa'id; Samra bin Jundub (Sunan Abi Dawud)
I testify that the Messenger of Allah (ﷺ) decided that the land is the land of Allah, and the servants are the servants of Allah. If anyone brings barren land into cultivation, he has more right to it. This tradition has been transmitted to us from the Prophet (ﷺ) by those who transmitted the traditions about prayer from him.
Grade: Da'if

Hadith #3230 - Sunan Abi Dawud - Abd al-Whab bin Ata'a عبد الوهاب بن عطاء الخفاف أبو نصر; Anas ibn Malik; Muhammad bin Abi Da'ud al-Bghdady محمد بن أبي داود; Qatada قتادة; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
Bashir’s name in pre-Islamic days was Zahm ibn Ma’bad. When he migrated to the Messenger of Allah (ﷺ). He asked: What is your name? He replied: Zahm. He said: No, you are Bashir. He (Bashir) said: When I was walking with the Messenger of Allah (ﷺ) he passed by the graves of the polytheists. He said: They lived before (a period of) abundant good. He said this three times. He then passed by the graves of Muslims. He said: They received abundant good. The Messenger of Allah (ﷺ) suddenly s
Grade: Sahih

Hadith #3277 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; Abdur Rahman bin Samra; al-Hasan al-Basri الحسن البصري; Qatada قتادة; Sa'id bin Abi Sa'id; Yahya bin Khlf al-Bahly يحيى بن خلف الباهلي أبو سلمة البصري (Sunan Abi Dawud)
The Prophet (ﷺ) said to me: ‘Abd al-Rahman b. Samurah, when you swear an oath and consider something else to be better than it, do the thing that is beter and make atonement for your oath. Abu Dawud said: I heard Ahmad (b. Hanbal) permitting to make atonement before breaking the oath.
Grade: Sahih

Hadith #3297 - Sunan Abi Dawud - Ikrama عكرمة; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Muhammad bin Abi 'Adi محمد بن أبي عدي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
That when the Prophet (ﷺ) was informed that the sister of ‘Uqbah b. ‘Amir had taken a vow to perform Hajj on foot, he said: Allah is not in need of her vow. So ask her to ride. Abu Dawud said: Sa’ib b. ‘Arubah has transmitted a similar tradition. Khalid has also transmitted a similar tradition on the authority of ‘Ikrimah from the Prophet (ﷺ).
Grade: Sahih

Hadith #3394 - Sunan Abi Dawud - Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Rafi' bin Khadij bin Rafi'; Sa'id bin Abi Sa'id; Sulayman ibn Yasar سليمان بن يسار مولى ميمونة بنت الحارث; Ubaidullah bin 'Umar al-Qawariri عبيد الله بن عمر القواريري; Y'la bin Hkym al-Thqfy يعلى بن حكيم الثقفي (Sunan Abi Dawud)
Ibn ‘Umar used to let out his land till it reached him that Rafi’ b. Khadij al-Ansari narrated that the Messenger of Allah (ﷺ) forbade let out land. So ‘Abd Allah (b. ‘Umar) said: Ibn Khadij, what do you narrate from the Messenger of Allah (ﷺ) about leasing the land? Rafi’ replied to ‘Abd Allah b. ‘Umar: I heard both of my uncles were present in the battle of Badr say, and they narrated it to the members of the family, that the Messenger of Allah (ﷺ) forbade leasing land. ‘
Grade: Sahih

Hadith #3500 - Sunan Abi Dawud - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Abu Thaur al-Kalbi إبراهيم بن خالد أبو ثور الكلبي; Anas ibn Malik; Qatada قتادة; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
A man told the Messenger of Allah (ﷺ) that he was being deceived in business transactions. The Messenger of Allah (ﷺ) then said: When you make a bargain, say: There is no attempt to deceive. So when the man made a bargain, he said: There is no attempt to deceive.
Grade: Sahih

Hadith #3536 - Sunan Abi Dawud - Abu Hurairah; Ibn Ishaq محمد بن إسحاق بن يسار‎; Kaysan Abu Sa'id al-Muqbari كيسان أبو سعيد المقبري المدني; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Sa'id bin Abi Sa'id; Salmah bin al-Fadl al-Abrash سلمة بن الفضل الأبرش (Sunan Abi Dawud)
That the Prophet (ﷺ) used to accept a gift and make return for it.
Grade: Sahih

Hadith #3570 - Sunan Abi Dawud - Abu Hurairah; Amr bin Abi 'Amr; Fdyl bin Sulaiman al-Nmyry فضيل بن سليمان النميري; Nasr bin 'Ali bin Nasr bin 'Ali; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
Al-Bara’ had a she-camel which was accustomed to graze the standing crop belonging to the people. She entered a garden and did damage to it. The Messenger of Allah (ﷺ) was informed about it. So he gave decision that the owners of gardens are responsible for guarding them by day, and the owners of the animals are responsible for guarding them by night. Any damage done by animals during the night is a responsibility lying on their owners.
Grade: Sahih

Hadith #3571 - Sunan Abi Dawud - Abdullah ibn Ja'far; Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu Hurairah; Nasr bin 'Ali bin Nasr bin 'Ali; Sa'id bin Abi Sa'id; Uthman bin Muhammad bin al-Mughira عثمان بن محمد بن المغيرة بن الأخنس (Sunan Abi Dawud)
The Prophet (ﷺ) said: He who has been appointed a judge has been killed without a knife.
Grade: Sahih

Hadith #3625 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; Ikrama عكرمة; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
A man from Muzainah who followed the knowledge and memorized it to me that sa’id b.al-Musayyab transmitted it. He then mentioned the rest of the tradition to the same effect.
Grade: Da'if

Hadith #3747 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
When the Prophet (ﷺ) returned to Medina, he would slaughter a camel or a cow.
Grade: Sahih

Hadith #3843 - Sunan Abi Dawud - Abu Hurairah; Ahmad bin Hanbal أحمد بن حنبل; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The tradition mentioned above (No. 3833) has also been transmitted by Ibn Abbas from Maymunah, from the Prophet (ﷺ) like the tradition narrated by az-Zuhri, from Ibn al-Musayyab.
Grade: Da'if

Hadith #3949 - Sunan Abi Dawud - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Muhammad bin Abi Da'ud al-Bghdady محمد بن أبي داود; Qatada قتادة; Sa'id bin Abi Sa'id; Umar ibn al-Khattab (Sunan Abi Dawud)
The Prophet (ﷺ) said: (The narrator Musa said in another place: From Samurah ibn Jundub as presumed by Hammad): If anyone gets possession of a relative who is within the prohibited degrees, that person becomes free. AbuDawud said: A similar tradition has also been transmitted by Samurah from the Prophet (ﷺ) through a different chain. Abu Dawud said: Only Hammad b. Salamah has transmitted this tradition and he had doubt in it.
Grade: Sahih

Hadith #3950 - Sunan Abi Dawud - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; al-Hasan al-Basri الحسن البصري; Qatada قتادة; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
Qatadah reported Umar ibn al-Khattab (may Allah be pleased with him) as saying: If anyone gets possession of a relative who is within the prohibited degrees, that person becomes free.
Grade: Da'if

Hadith #3951 - Sunan Abi Dawud - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Hammad bin Usamah حماد بن أسامة - أبو أسامة; Jabir bin Zayd al-Azdi جابر بن زيد الأزدي; Qatada قتادة; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
If anyone gets possession of a relative who is within the prohibited degrees, that person becomes free.
Grade: Da'if

Hadith #4197 - Sunan Abi Dawud - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sa'id bin Abi Sa'id; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
Al-Hajjaj ibn Hassan said: We entered upon Anas ibn Malik. My sister al-Mughirah said: You were a boy in those days and you had two locks of hair. He (Anas) rubbed your head and invoked blessing on you. He said: Shave them (i.e. the locks) or clip them, for this is the fashion of the Jews.
Grade: Da'if

Hadith #4213 - Sunan Abi Dawud - Anas ibn Malik; Isa bin Yonus bin Abi Ishaq عيسى بن يونس بن أبي إسحاق; Qatada قتادة; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
When the Messenger of Allah (ﷺ) went on a journey, the last member of his family he saw was Fatimah, and the first he visited on his return was Fatimah. Once when he returned from an expedition she had hung up a hair-cloth, or a curtain, at her door, and adorned al-Hasan and al-Husayn with silver bracelets. So when he arrived, he did not enter. Thinking that he had been prevented from entering by what he had seen, she tore down the curtain, unfastened the bracelets from the boys and cut them o
Grade: Da'if

Hadith #4214 - Sunan Abi Dawud - Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Qatada قتادة; Sa'id bin Abi Sa'id; Wahb bin Bqyh bin 'Uthman وهب بن بقية بن عثمان (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) wanted to write to some persian rulers. He was told that they would not read a letter without a seal in the form of a silver ring on which he engraved “Muhammad the Messenger of Allah.”
Grade: Sahih

Hadith #4459 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; al-Hasan al-Basri الحسن البصري; Qatada قتادة; Sa'id bin Abi Sa'id; Salmah bin al-Mahbaq (Sunan Abi Dawud)
The Prophet (ﷺ) said: about a man who had (unlawful) intercourse with his wife’s slave girl: If she made her lawful for him, he will be flogged one hundred lashes; if she did not make her lawful for him, I shall stone him.
Grade: Hasan

Hadith #4468 - Sunan Abi Dawud - Abu Hurairah; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sa'id bin Abi Sa'id; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
A man came to the Prophet (ﷺ) and said: I contacted directly a women at the furthest part of the city (i.e., Medina), and I did with her everything except sexual intercourse. So here I am; inflict any punishment you wish. Thereupon ‘Umar said: Allah has concealed your fault; it would have been better if you also had concealed it yourself. The Prophet (ﷺ) sent a men after him. (When he came) he recited the verse: “And establish regular prayers at the two ends of the day and at the approac
Grade: Hasan Sahih

Hadith #4469 - Sunan Abi Dawud - Abu Hurairah; Ibn Ishaq محمد بن إسحاق بن يسار‎; Kaysan Abu Sa'id al-Muqbari كيسان أبو سعيد المقبري المدني; Muhammad bin Salmah محمد بن سلمة بن عبد الله الباهلي; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) was asked about a slave-woman who commits fornication, and she is not married: If she commits fornication, flog her: if she commits fornication again flog her; if only for a rope of hair (dafir). Ibn Shihab: I do not know whether he (the Prophet) said it is a third or a fourth time.
Grade: Sahih

Hadith #4502 - Sunan Abi Dawud - Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Sa'id bin Abi Sa'id; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
We were with Uthman when he was besieged in the house. There was an entrance to the house. He who entered it heard the speech of those who were in the Bilat. Uthman then entered it. He came out to us, looking pale. He said: They are threatening to kill me now. We said: Allah will be sufficient for you against them, Commander of the Faithful! He asked: Why kill me? I heard the Messenger of Allah (ﷺ) say: It is not lawful to kill a man who is a Muslim except for one of the three reasons: Kufr (d
Grade: Sahih

Hadith #4507 - Sunan Abi Dawud - Aabad bin al-Wam bin عباد بن العوام; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Da'ud bin Rshyd داود بن رشيد; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Sa'id bin Abi Sa'id; Sa'id bin Sulaiman al-Dabi سعيد بن سليمان - سعدويه الضبي; Sufyan bin Hussain bin al-Hasan سفيان بن حسين السلمي (Sunan Abi Dawud)
The Prophet (ﷺ) said: I will not forgive anyone who kills after accepting blood-wit
Grade: Da'if

Hadith #4552 - Sunan Abi Dawud - Amr bin al-Aswad al-Ansi عمرو بن الأسود العنسي; Muhammad bin 'Abdullah bin Qahzad محمد بن عبد الله بن قهزاد; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة; Sa'id bin Abi Sa'id; Uthman ibn 'Affaan (Sunan Abi Dawud)
The bloodwit for unintentional murder is in four parts: twenty five she-camels in their fourth year, twenty five she-camels in their fifth year, twenty five she-camels in their third year, and twenty twenty five she-camels in their second year.
Grade: Da'if

Hadith #4553 - Sunan Abi Dawud - Abu Da'ud أبو داود السجستاني الأزدي; al-Qasim bin Salam القاسم بن سلام; Muhammad bin 'Abdullah bin Qahzad محمد بن عبد الله بن قهزاد; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة; Sa'id bin Abi Sa'id; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Zayd ibn Thabit (Sunan Abi Dawud)
The bloodwit for what resembled intentional murder should be forty pregnant she-camels in their fifth year, thirty she-camels in their fourth year, and thirty she-camels in their third year. The bloodwit for unintentional murder is thirty she-camels in their fourth year, thirty she-camels in their third year, and twenty she-camels in their second year.
Grade: Da'if

Hadith #4672 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; Ma'mar bin Rashid معمر بن راشد; Mkhld bin Khalid bin Yazid مخلد بن خالد بن يزيد الشعيري; Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Muhammad bin Abi Sari محمد بن أبي السري; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
A man said to the Messenger of Allah (May peace be upon him): O best of all creatures! The Messenger of Allah (May peace be upon him) said : That was Abraham (peace be upon him).
Grade: Sahih

Hadith #4688 - Sunan Abi Dawud - Abu Hurairah; Ishaq bin Ibrahim bin Swyd إسحاق بن إبراهيم بن سويد; Nafi' bin Yazid al-Kula'i نافع بن يزيد الكلاعي; Sa'id bin Abi Maryam سعيد بن أبي مريم; Sa'id bin Abi Sa'id; Yazid bin 'Abdullah bin Usama B. al-Haad يزيد بن عبد الله بن أسامة بن الهاد (Sunan Abi Dawud)
Four characteristics constitute anyone who possesses them a sheer hypocrite, and anyone who possesses one of them possesses a characteristics of hypocrisy till he abandons it : when he talks he lies, when he makes a promise he violates it, when he makes a covenant he acts treacherously, and when he quarrels, he deviates from the Truth.
Grade: Sahih

Hadith #4749 - Sunan Abi Dawud - Anas ibn Malik; Muhammad bin Abi Da'ud al-Bghdady محمد بن أبي داود; Qatada قتادة; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
I saw AbuBarzah who came to visit Ubaydullah ibn Ziyad. Then a man named Muslim who was there in the company mentioned it to me. When Ubaydullah saw him, he said: This Muhammadan of yours is short and fat. The old man (i.e. AbuBarzah) understood it. So he said: I did not think I would remain amongst a people who would criticize me for having had the company of Muhammad (ﷺ). Thereupon Ubaydullah said to him: The company of Muhammad (ﷺ) is a honour for you, not a disgrace. He added: I called f
Grade: Sahih

Hadith #4814 - Sunan Abi Dawud - Abdur Rahman bin Ishaq عبد الرحمن بن إسحاق بن عبد الله; Abu Hurairah; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Prophet (ﷺ) said: If someone is donated something, and he mentions it, he thanks for it, and if he conceals it, he is ungrateful for it.
Grade: Sahih

Hadith #4854 - Sunan Abi Dawud - Abu Hurairah; al-Laith bin Sa'd الليث بن سعد; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) would sit and we would also sit around him. If he got up intending to return, he would take off his sandals or something he was wearing, and his Companions recognising his purpose (that he would return) would stay where they were.
Grade: Da'if

Hadith #4855 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Amr bin al-Harith bin Ya'qub عمرو بن الحارث; Sa'id bin Abi Hilal سعيد بن أبي هلال الليثي; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Prophet (ﷺ) said: People who get up from an assembly in which they did not remember Allah will be just as if they had got up from an ass’s corpse, and it will be a cause of grief to them.
Grade: Sahih

Hadith #4856 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Amr bin al-Harith bin Ya'qub عمرو بن الحارث; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone sits at a place where he does not remember Allah, deprivation will descend on him from Allah; and if he lies at a place where he does not remember Allah, deprivation will descend on him from Allah.
Grade: Hasan Sahih

Hadith #4894 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; Isa bin Hammad bin Muslim, Zaghba عيسى بن حماد بن مسلم أبو موسى زغبة; Sa'id bin Abi Sa'id; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan Abi Dawud)
when two men abuse one another, what they say is laid to the charge of the one who began it, so long as the one who is wronged does not go over the score.
Grade: Sahih

Hadith #4895 - Sunan Abi Dawud - Abdul A'ala bin Hamad bin Nasr al-Bahli عبد الأعلى بن حماد بن نصر الباهلي النرسي; Abu Hurairah; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Sa'id bin Abi Sa'id; Safwan bin 'Isa al-Zhry صفوان بن عيسى الزهري أبو محمد البصري; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) said: Allah has revealed to me that you must be humble, so that no one oppresses another and boasts over another.
Grade: Sahih

Hadith #5011 - Sunan Abi Dawud - Ahmed bin 'Ubda bin Musa أحمد بن عبدة بن موسى; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Sa'id bin Abi Sa'id; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
A desert Arab came to the Prophet (ﷺ) and began to speak. Thereupon the Messenger of Allah (ﷺ) said: In eloquence there is magic and in poetry there is wisdom.
Grade: Sahih

Hadith #5026 - Sunan Abi Dawud - Abu Hurairah; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Kaysan Abu Sa'id al-Muqbari كيسان أبو سعيد المقبري المدني; Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Sa'id bin Abi Sa'id; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
When one of you yawns, he should hold his hand over his mouth, for the devil enters.
Grade: Sahih

Hadith #5032 - Sunan Abi Dawud - Abu Hurairah; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Sa'id bin Abi Sa'id; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The tradition mentioned above (No. 5013) has also been mentioned by Salim ibn Ubayd al-Ashja’i to the same effect from the Prophet (ﷺ) through a different chain of narrators.
Grade: Da'if

Hadith #5033 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; Isa bin Hammad bin Muslim, Zaghba عيسى بن حماد بن مسلم أبو موسى زغبة; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
When one of you sneezes, he should say: “Praise be to Allah in every circumstance,” and his brother or his companion should say: “May Allah have mercy on you!” And he should then reply: “May Allah guide you and set right your affairs.”
Grade: Sahih

Hadith #5048 - Sunan Abi Dawud - Abu Hurairah; Kaysan Abu Sa'id al-Muqbari كيسان أبو سعيد المقبري المدني; Sa'id bin Abi Sa'id; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
when you go to your bed while you are in the state of purification. The other said: Perform ablution like the ablution for prayer. He then transmitted the tradition to the effect as Mu’tamir transmitted.
Grade: Sahih

Hadith #5057 - Sunan Abi Dawud - Abu Hurairah; al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) used to recite al-Musabbihat before going to sleep, and say: They contain a verse which is better than a thousand verses.
Grade: Hasan

Hadith #5106 - Sunan Abi Dawud - ibn Abbas; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Nasr bin 'Ali bin Nasr bin 'Ali; Qatada قتادة; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
Boys used to be brought to the Messenger of Allah (ﷺ), and he would invoke blessings on them. Yusuf added: “and soften some dates and rub their palates with them”. He did not mention “blessings”.
Grade: Sahih

Hadith #5114 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Ahmed bin Sa'id bin Sakhar أحمد بن سعيد بن صخر; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Kaysan Abu Sa'id al-Muqbari كيسان أبو سعيد المقبري المدني; Musa bin Mrwan موسى بن مروان; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
if a man becomes the client of any people without the permission of his patrons (i.e. those who have freed him), on him will be the curse of Allah, of angels and of all people; no obligatory or supererogatory worship will be accepted from him.
Grade: Sahih

Hadith #5206 - Sunan Abi Dawud - Abu Hurairah; Ahmad bin Hanbal أحمد بن حنبل; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Prophet (ﷺ) said: When one of the Jews greets you saying: Death may come upon you, reply: The same to you. Abu Dawud said: Malik b. ‘Adb Allah b. Dinar transmitted it in a similar manner, and al-Thawri transmitted it from ‘Abd Allah b. Dinar. He said in this version: The same to you.
Grade: Sahih

Hadith #5272 - Sunan Abi Dawud - Abu Hurairah; Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Sa'id bin Abi Sa'id; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
AbuUsayd heard the Messenger of Allah (ﷺ) say when he was coming out of the mosque, and men and women were mingled in the road: Draw back, for you must not walk in the middle of the road; keep to the sides of the road. Then women were keeping so close to the wall that their garments were rubbing against it.
Grade: Hasan